Medial Efferent Mechanisms in Children with Auditory Processing Disorders - Mishra, Srikanta K. (Frontiers in Human Neuroscience, 2014)
Auditory processing disorder (APD) affects about 2 to 5% of children. However, the nature of this disorder is poorly understood. Children with APD typically have difficulties in complex listening situations. One mechanism thought to aid in listening-in-noise is the medial olivocochlear (MOC) inhibition. The purpose of this review was to critically analyze the published data on MOC inhibition in children with APD to determine whether the MOC efferents are involved in these individuals. The otoacoustic emission (OAE) methods used to assay MOC reflex were examined in the context of the current understanding of OAE generation mechanisms. Relevant literature suggests critical differences in the study population and OAE methods. Variables currently known to influence MOC reflex measurements, for example, middle-ear muscle reflexes or OAE signal-to-noise ratio, were not controlled by most studies. The use of potentially weaker OAE methods and the remarkable heterogeneity across studies does not allow for a definite conclusion whether or not the MOC reflex is altered in children with APD. Further carefully designed studies are needed. Knowledge of efferent functioning in children with APD would be mechanistically and clinically beneficial.